{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

partimes - Amdahl Parallel Performance Mohamed Iskandarani...

Info iconThis preview shows pages 1–9. Sign up to view the full content.

View Full Document Right Arrow Icon
Amdahl Parallel Performance Mohamed Iskandarani December 2, 2008
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full Document Right Arrow Icon
Amdahl Outline Amdahl
Background image of page 2
Amdahl Amdahl’s law Definitions: t s ( P ) execution time of serial portion on P processors t p ( P ) execution time of parallel portion on P processors Speedup = time on 1 processors time on P processors = t s ( 1 ) + t p ( 1 ) t s ( P ) + t p ( P ) Assumptions 1. uniform serial time: t s ( 1 ) = t s ( P ) = t s . 2. parallel overhead is negligeable: t 1 ( P ) = Pt p ( P )
Background image of page 3

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full Document Right Arrow Icon
Amdahl Amdahl’s law S = t s + t p ( 1 ) t s + t p ( 1 ) P = 1 t s t s + t 1 ( p ) + t p ( 1 ) P [ t s + t p ( 1 )] (1) = 1 β A + 1 - β A P (2) β A = t s t s + t 1 ( P ) = serial fraction (3)
Background image of page 4
Amdahl Amdahl’s law for fixed β A 0 200 400 600 800 1000 1200 0 10 20 30 40 50 60 70 80 90 100 β A =0.01 β A =0.10 β A =0.50 S P
Background image of page 5

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full Document Right Arrow Icon
Amdahl Amdahl’s law for fixed P 10 -7 10 -6 10 -5 10 -4 10 -3 10 -2 10 -1 10 0 0 0.1 0.2 0.3 0.4 0.5 0.6 0.7 0.8 0.9 1 β S max /P P=128 P=256 P=512 P=1024
Background image of page 6
Amdahl Gustafson’s law S = t s + Pt p ( P ) t s + t p ( P ) = t s t s + t p ( P ) + P t p ( P ) t s + t p ( p ) = β G + P ( 1 - β G ) β G = t s t s + t p ( P ) = scaled serial fraction
Background image of page 7

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full Document Right Arrow Icon
Amdahl Amdahl-Gustafson’s equivalence ( 1 - β A ) t s = β A t p ( 1 ) ( 1 - β G ) t s = β G t p ( P ) ( 1 - β A ) ( 1 - β G ) = P β A β G
Background image of page 8
Image of page 9
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}